2023
DOI: 10.1002/mp.16191
|View full text |Cite
|
Sign up to set email alerts
|

Flexible real‐time skin dosimeter based on a thin‐film copper indium gallium selenide solar cell for electron radiation therapy

Abstract: Purpose Various dosimeters have been proposed for skin dosimetry in electron radiotherapy. However, one main drawback of these skin dosimeters is their lack of flexibility, which could make accurate dose measurements challenging due to air gaps between a curved patient surface and dosimeter. Therefore, the purpose of this study is to suggest a novel flexible skin dosimeter based on a thin‐film copper indium gallium selenide (CIGS) solar cell, and to evaluate its dosimetric characteristics. Methods The CIGS sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The nature of the aforementioned thermal effects has not been fully elucidated. The authors of [7] explain their presence as a result of the processes of glass splitting of the amorphous phase of the samples.…”
Section: Methods Of Thermoluminescence Measurements Of Thin-film Stru...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the aforementioned thermal effects has not been fully elucidated. The authors of [7] explain their presence as a result of the processes of glass splitting of the amorphous phase of the samples.…”
Section: Methods Of Thermoluminescence Measurements Of Thin-film Stru...mentioning
confidence: 99%
“…The study of such phenomena is of particular interest in connection with the prospects of using thin-film structures for dosimetric measurements [5][6][7][8]. Their advantages are compactness, suitability for measuring the absorbed dose in thin layers, particularly in the skin, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…43 Shin et al reported that flexible CIGS solar cells can be used as a skin dosimeter for 6− 16 MeV electron beam therapy. 44 Notably, the energy of electrons typically used in such high-energy electron beam therapy devices lies in the range of 6−10 MeV. Thus, further investigation is required to clarify the effects of electron beam irradiation on perovskite and the corresponding mechanisms, especially beyond 1 MeV.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Jeong et al demonstrated that a-Si solar cells can be applied to electron beam therapy as a real-time in vivo dosimetry system in the electron energy range of 6–20 MeV . Shin et al reported that flexible CIGS solar cells can be used as a skin dosimeter for 6–16 MeV electron beam therapy . Notably, the energy of electrons typically used in such high-energy electron beam therapy devices lies in the range of 6–10 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…A defect is considered to be shallow when its energy level is very close to the minima of a conduction band or very close to maxima of a valence band [8], otherwise it is regarded as a deep defect. Deep defects are very common in many doped materials [8,9,10]. They are considered to be free carrier traps known to capture charge carriers that are introduced through doping [9].…”
Section: Introductionmentioning
confidence: 99%